RANK-Fc inhibits malignancy via inhibiting ERK activation and evoking caspase-3-mediated anoikis in human osteosarcoma cells - Akiyama, T.; Choong, P.; Dass, Crispin (Springer Netherlands, 2010)
Osteosarcoma (OS) is the most common primary malignant bone tumour, mainly afflicting the young. While there has been substantial improvement in treatment of OS with surgery and chemotherapy in the past two decades, this disease remains a significant health problem, warranting efforts to find better therapeutic options. In this study, we examined the RANK/RANKL axis in OS cells, using a RANK-Fc protein to perturb this coupling in an effort to reduce OS cell growth. RANK-Fc suppressed OS cell migration (P < 0.005), invasion ability (P < 0.05), and anchorage-independent ability in collagen-1 gel (P < 0.005) following induction of anoikis and activation of caspase-3. OS cell proliferation was not perturbed by RANK-Fc. The anti-invasion and anti-metastasis capability of RANK-Fc is attributed to reduced extracellular signal-regulated protein kinase (ERK) signaling via RANK-Fc, though activation of NF?B, and altered expression of Akt, p38, JNK, and matrix metalloproteinase (MMP)-2 and -9 were ruled out. In vivo, activity of the RANK-Fc against OS cell migration and invasion was confirmed in a model strictly monitoring metastasis. Thus, RANK-Fc, given its ability to directly reduce OS aggression, is a potential drug candidate.